Análisis Económico de las Exportaciones de Cacao en Colombia durante el periodo 2010-2020 (2022)
The objective of this document is to provide data and general information on the cultivation of cocoa in Colombia and its agribusiness, emphasizing the department of Huila, as well as the historical behavior of imports and exports of said product. It begins with a brief description of the planted areas and their production, in order to establish the respective performance, and thus achieve the main figures of the sector at the international level through exports and their behavior over time, in terms of area. planted, production, export and yields. Exhibiting in the same way the changes in the price and its national market as well as its influence on the international market. Bearing in mind the different economic activities generated with the production of cocoa, explaining the different positive aspects in the population, such as the increase in employment